Ammonia Exposure Based on the Length of Work to Lung Function Abnormalities Among Traditional Scavengers - Jasmine, Maulyda Shakeela; Nurcandra, Fajaria; Fithri, Nayla Kamilia; Buntara, Arga (UI Scholars Hub, 2024)
Lung function abnormalities can be caused by smoking habits or air pollution. Sanitary landfills can produce ammonia, which can cause lung function abnormalities. This study aimed to determine a relationship between ammonia exposure based on the length of work and lung function abnormalities among traditional scavengers at the Sumur Batu Landfill, Bekasi City, West Java Province, Indonesia. This analytical observational study applied quantitative methods and cross-sectional design. A total of 85 scavengers were selected using purposive sampling from March to May 2023. Data was obtained using a respondent characteristics questionnaire, spirometry, and spectrophotometer and analyzed using the Cox Regression Model. Most respondents (54.12%) had lung function abnormalities, and 79.17% had worked ≥8.5 years. The adjPR of ammonia exposure based on the length of work to lung function abnormalities was 3.413 (95% CI 1.51—7.71). There were confounding variables between ammonia exposure based on the length of work and lung function abnormalities: smoking status and lung disease record. In conclusion, ammonia exposure based on the length of work strongly correlates with lung function abnormalities in scavengers after adjusting for the lung disease record and smoking behavior.